Inside Back Cover: Intramolecular Carbolithiation of Heterosubstituted Alkynes: An Experimental and Theoretical Study (Chem. Eur. J. 22/2015). Issue 22 (26th May 2015) - Lhermet, Rudy; Ahmad, Maha; Hauduc, Clémence; Fressigné, Catherine; Durandetti, Muriel; Maddaluno, Jacques
<x xml:space="preserve">Abstract</x> The regio‐ and stereoselectivity of the carbolithiation of heterosubstituted alkynes depends on the heteroelement borne by the triple bond. If the heteroelement coordinates Li+, a 5‐exo‐dig anti addition is observed, and the product has an E configuration. The opposite pathway is followed if the lithium has no affinity for the substituent—the addition is syn and the product Z. Another deviance is observed with N‐phosphoryl ynamide for which cyclization evolves with a 6‐endo‐dig route. These competitive itineraries depend on the LiX affinity that acts as the primary driving force. The entangled bifurcations symbolized on the picture illustrate this point. For more information, see the Full Paper by M. Durandetti, J. Maddaluno and co‐workers on page 8105 ff.